Första svenska ordboken – tankar bakom en barnordbok - Gellerstam, Martin; Malmgren, Sven-Göran (Nordiske Studier i Leksikografi, 2003)
A Swedish dictionary for children (Norstedts första svenska ordbok) has been published recently, containing some ten thousand conventional words and about two thousand encyclopedic words. This paper is a presentation of the dictionary, focussing mainly on the definition format which has been inspired by the Cobuild style of definition. In many ways this format is well suited for a children’s dictionary and especially for explaining difficult words – if you are willing to make definitions somewhat less general in order to make them intelligible.